أثر عامل المخاطرة على عائد المحافظ المالية " دراسة قياسية لعينة من المحافظ بالسوق المالي السعودي خلال الفترة 2021-2023 " - بن داود, آمنة; ولد عابد, عمر (جامعة الوادي - University of Eloued, 2023)
This study aimed to measure the impact of the risk factor on the return of financial portfolios for a sample of portfolios in the Saudi financial market during the period (2021q2- 2023q2). The current study relied on quarterly data with a totalof 9 observations for each portfolio. The study sample included (Al-Emaar Portfolio, Al-Shujaa Portfolio, Balanced Portfolio, Al-Jari Portfolio, and the Small and Medium companies Portfolio). The results of estimating the static model for panel data using the Eviews 12 program showed: The sign of the parameter associated with portfolio risk (SDD) has a negative sign and therefore had an inverse effect on the portfolio return. Whereas an increase in the risk of the financial portfolio by: 100% leads to a decline in the financial portfolio return index by: 176%, It is a high flexibility that reflects the impact of financial portfolio risks on their retur
The impact of the risk factor on the return of financial portfolios“ A benchmark study of a sample of portfolios in the Saudi financial market during the period 2021-2023
مقال
Keywords: المحفظة المالية ; المخاطر المالية ; عائد المحفظة المالية ; نماذج بانل; :Portfolio, Financial risks, return of financial portfolio, Panel mode